Functional outcomes after internal and external hemipelvectomy in HUSM - Sharifudin, Mohd Ariff; Wan, Zulmi; Wan Ismail, Wan Faisham Numan; Mat Zin, Nor Azman; Mohamed Amir, Nawaz Hussain (2012)
Background: Although great advancements have been made in survival rates over the last half century with adjuvant therapies and current surgical techniques, hemipelvectomy as the surgical treatment for pelvic tumours continue to have significant associations with morbidity and complications. Using the Enneking’s criteria as adopted by the Musculoskeletal Tumor Society (MSTS), we evaluated the functional outcomes of patients who have had an internal hemipelvectomy with and without reconstruction, and external hemipelvectomy. Method: We evaluated patients who underwent hemipelvectomy in our institution between 2001 and 2010. Patients who had had an internal or external hemipelvectomy surgery at any point in their clinical course were included in the study. Patients with follow up periods of less than four months were not included. MSTS scores were obtained at various times after the surgery. Results: A total of 50 patients who had undergone various types of resection and reconstruction techniques were included in this study. The average age is 40.1 years (range 12-79). Average duration of follow up is 10 months. The average MSTS percentage score was 44.32% (range: 6.67%-100%). Results show that external hemipelvectomy in our patients have a high morbidity and mortality rate. Various techniques of resection and reconstruction give different functional scores. Conclusion: Hemipelvectomies have a profound impact on patients’ lives as illustrated by their low MSTS scores. Proper patient selection is crucial to obtain the best outcome. This study is an effort to obtain a proper reference for preoperative discussion with patients and relatives regarding expected outcomes following such a procedure.